FNKSDA SEBAGAI WUJUD GERAKAN ISLAM NUSANTARA “HIJAU’ - Listiana Asworo; Nuruddin Al Akbar (IAIN Manado, 2019)
Abstract. This study seeks to get out of mainstream thinking in environmental studies that are based on Eurocentric logic. Mainstream studies emphasize the